(untitled) (Cessie : Jurnal Ilmiah Hukum, 2025)
This study is to create an approach between local development and tourism in order to assess whether or not tourism may be a strategy in local community empowerment. The objective of this research is to build an approach between local development and tourism. In the offered text, evolution, conceptualization, and components are discussed. In this study, we use a qualitative approach and combine it with a descriptive methodology. The data used in this study originated from a variety of different literatures that were pertinent to this investigation. The findings that were gathered indicate that there are a variety of perspectives held by members of the community who are seen as crucial participants in the process. In this research, it is also emphasized that tourism cannot be the sole source of revenue; rather, it should be seen as an activity that contributes to the overall improvement of the community’s quality of life. neighboring areas with an emphasis on fostering community empowerment within those communities.